An Algal Diet Accelerates Larval Growth of Anopheles gambiae (Diptera: Culicidae) and Anopheles arabiensis (Diptera: Culicidae). Issue 3 (21st January 2018) - Tuno, N; Kohzu, A; Tayasu, I; Nakayama, T; Githeko, A; Yan, G
Abstract: The population sizes of Anopheles gambiae Giles (Diptera: Culicidae) and Anopheles arabiensis Patton (Diptera: Culicidae) increase dramatically with the onset of the rainy season in sub-Saharan Africa, but the ecological mechanisms underlying the increases are not well understood. As a first step toward to understand, we investigated the proliferation of algae, the major food of mosquito larvae, in artificial fresh water bodies exposed to sunlight for a short period, and old water bodies exposed to sunlight for a long period, and the effects thereof on the development of these anopheline larvae. We found that an epizoic green algal species of the genus Rhopalosolen (Chlorophyta: Chlorophyceae) proliferated immediately after water freshly taken from a spring was placed in sunlight. This alga proliferated only briefly (for ~10 d) even if the water was repeatedly exposed to sunlight. However, various algal species were observed in water that remained under sunlight for 40 d or longer (i.e., in old water bodies). The growth performance of larvae was higher in sunlight-exposed (alga-rich) water than in shade-stored (alga-poor) water. Stable isotope analysis suggested that these two anopheline species fed on Rhopalosolen algae in fresh water bodies but hardly at all on other algae occurring in the old water bodies. We concluded that freshly formed ground water pools facilitate high production of anopheline species because of the proliferation of Rhopalosolen algae therein, and the increase in the number of such pools in the rainy season, followed by rapid increases in A. gambiae and A. arabiensis numbers.